Tendon Tissue Repair in Prospective of Drug Delivery, Regenerative Medicines, and Innovative Bioscaffolds - Muhammad Nadeem Hafeez; Nicola d'Avanzo; Valentina Russo; Luisa Di Marzio; Felisa Cilurzo; Donatella Paolino; Massimo Fresta; Barbara Barboni; Hélder A. Santos; Christian Celia (Hindawi Limited, 2021)
The natural healing capacity of the tendon tissue is limited due to the hypovascular and cellular nature of this tissue. So far, several conventional approaches have been tested for tendon repair to accelerate the healing process, but all these approaches have their own advantages and limitations. Regenerative medicine and tissue engineering are interdisciplinary fields that aspire to develop novel medical devices, innovative bioscaffold, and nanomedicine, by combining different cell sources, biodegradable materials, immune modulators, and nanoparticles for tendon tissue repair. Different studies supported the idea that bioscaffolds can provide an alternative for tendon augmentation with an enormous therapeutic potentiality. However, available data are lacking to allow definitive conclusion on the use of bioscaffolds for tendon regeneration and repairing. In this review, we provide an overview of the current basic understanding and material science in the field of bioscaffolds, nanomedicine, and tissue engineering for tendon repair.